Komparasi Treatment Planning Pada Kanker Leher Rahim Menggunakan Teknik 3DCRT dan IMRT: COMPARISON OF TREATMENT PLANNING IN CERVIX CANCER USING 3DCRT AND IMRT TECHNIQUES - suwandi; Damayanti, Oktarina; Ningrum, Surdiyah Asri (JURNAL TERAS KESEHATAN, 2023)
Cancer is a non-communicable disease that is still a health problem in the world, including Indonesia. About 50 percent of cancer treatments worldwide are performed using radiotherapy. In its implementation, radiotherapy includes several stages, one of which is treatment planning. This study aims to assess the difference in dose received by PTV and OARs in planning using IMRT and 3DCRT techniques in cervical cancer patients. The method used in this study is scanning using a CT simulator, delineating PTV and healthy organs around the tumor (OARs), and planning using treatment planning system software. The results showed that in OARs, 3DCRT planning resulted in a dose of 4000 cGy by hitting 58.28% of the buli volume, and a dose of 5000cGy by hitting 17.76% of the rectum volume. While planning IMRT, a dose of 4000cGy hits 31.50% of the buli volume, and a dose of 5000cGy hits 12.29% of the rectum volume. In PTV, the doses produced by 3DCRT and IMRT planning were 4750cGy and 4750 cGy, and hit 95.18% and 98.71% of PTV volume, respectively. This study concludes that planning using IMRT is better than planning using 3DCRT in cases of cervical cancer. This is shown by the dose that covers the target tumor (PTV) and a significant dose reduction in OARs.